2019
DOI: 10.1002/1873-3468.13558
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of retro‐isomer equilibrium structures: Intrinsically disordered, foldable, and cyclic peptides

Abstract: We use all-atom modeling and advanced-sampling molecular dynamics simulations to investigate quantitatively the effect of peptide bond directionality on the equilibrium structures of four linear (two foldable, two disordered) and two cyclic peptides. We find that the retro forms of cyclic and foldable linear peptides adopt distinctively different conformations compared to their parents. While the retro form of a linear intrinsically disordered peptide with transient secondary structure fails to reproduce a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
5
0
1
Order By: Relevance
“…Recently, Zerze et al investigated the effect of sequence reversal on the conformational preferences of a number of peptide systems, including two cyclic peptides: cyclo-(GHGAYG) and cyclo-(GRCTKSIPPICFPD), the latter of which also contains a disulfide bridge between the cysteine residues . The authors performed PTWTE simulations using the AMBER-03w force field and the TIP4P/2005 water model .…”
Section: Using MD Simulations To Elucidate the Solution Structures Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zerze et al investigated the effect of sequence reversal on the conformational preferences of a number of peptide systems, including two cyclic peptides: cyclo-(GHGAYG) and cyclo-(GRCTKSIPPICFPD), the latter of which also contains a disulfide bridge between the cysteine residues . The authors performed PTWTE simulations using the AMBER-03w force field and the TIP4P/2005 water model .…”
Section: Using MD Simulations To Elucidate the Solution Structures Of...mentioning
confidence: 99%
“…274,275 Recently, Zerze et al investigated the effect of sequence reversal on the conformational preferences of a number of peptide systems, including two cyclic peptides: cyclo-(GHGAYG) and cyclo-(GRCTKSIPPICFPD), the latter of which also contains a disulfide bridge between the cysteine residues. 276 The authors performed PTWTE simulations using the AMBER-03w force field 277 and the TIP4P/2005 water model. 236 Seven replicas in the 300−450 K range were used for each system, with a bias factor of 10 for cyclo-(GHGAYG) and 16 for cyclo-(GRCTKSIPPICFPD); the replicas were run for at least 300 ns for each system.…”
Section: Sequence Reversal Effect On Cyclic Peptide Structure [Ptwte]mentioning
confidence: 99%
“…[21][22][23][24][25][26] Partial retro-isomer structure was successfully applied to several families of biological active peptides. For example, retro-isomer of tumor suppressor protein p53 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) had strong binding affinity to MDM2, which is a human E3 ubiquitin ligase that mediates ubiquitination of p53/TP53. 21 As expected, the strategy is not universally applicable because the retro-isomer may have different three-dimentional structure from the original one.…”
Section: Introductionmentioning
confidence: 99%
“… 21 As expected, the strategy is not universally applicable because the retro-isomer may have different three-dimentional structure from the original one. 27 Li et al reported that stingin emulated the transactivation peptide of p53 and bound with high affinity to MDM2, while its retro isomer completely abolished its MDM2 binding. 28 Although, the retro-isomer transformation remains an important peptide modification method and has been widely used for designing novel and proteolytically stable peptides with comparable biological activities by numerous bioorganic chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Retro Trp-cage [21,29,30] SPPPRGSSPGGDKLWQIYLN a) 符号"-"表示蛋白序列的其他省略部分; 残基D-Ala突变在序 列中显示为"a"; TC5b的D9N突变在文献中为TC6a [24] 或TC5c体 系 [25] , 在此统称为TC6a体系; TC5b的D9E突变体称为TC6b体系 [24] 态两种结构态, 不形成中间态结构, 显示为单指数弛豫 动力学 [17] . Qiu和Streicher等人 [17,46] 使用差示扫描量热 法(differential scanning calorimetry, DSC)、圆二色谱 (circular dichroism, CD)和激光温度跃迁(laser temperature-jump, LT-J)光谱等实验方法, 以及Snow和Day等 人 [47,48] 分别通过Folding@Home项目和副本交换分子 动力学(replica exchange molecular dynamics, REMD)…”
unclassified